Assessment of Tobacco Consumption and Control in India. (2nd March 2018) - Mohan, Priya; Lando, Harry A; Panneer, Sigamani
Tobacco consumption is a huge public health issue in India and its impact is especially devastating among the poor. Effective tobacco control should be a top priority, both as a health issue and as a method to reduce poverty. Tobacco use is deeply ingrained as a cultural practice and there are a myriad of tobacco types. We reviewed multiple determinants of tobacco consumption including socio-economic status, marriage, population growth, marketing strategies, and price. We also considered the tobacco burden including economic and social costs and adverse health impacts especially those resulting from oral cancer. We then addressed the history of tobacco control legislation in India and challenges in implementation. Tobacco consumption in India is continuing to increase despite tobacco control policy. Needed are more visible and aggressive anti-tobacco campaigns including increased public awareness of tobacco harms and active engagement of worksites and health professionals in promoting tobacco cessation.